2018
DOI: 10.1111/jopr.12791
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of the Effect of Various Adhesives and Surface Treatments on Bond Strength of Resin Cement to Polyetheretherketone

Abstract: Silica coating and sandblasting were shown to provide superior pretreatment of PEEK surface. Laser pretreatments showed no effectiveness on bond strength of resin cement to PEEK. Adhesive systems improved the resin bonding to PEEK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 23 publications
6
79
0
Order By: Relevance
“…PEEK frameworks have a grayish-brown or pearl-white opaque color and need to be veneered with a composite resin. Several studies on bond strength of PEEK with composite resins have proposed different pre-treatments such as airborne-particle abrasion, silica coating [ 63 ], piranha-etching [ 64 ], sulfuric acid [ 65 ], phosphoric acid or argon plasma [ 66 ] with conflicting results. However, most of the studies concluded that reliable bond strength to composite veneering resins and luting cements can be achieved when PEEK surfaces are pretreated and conditioned using adhesive systems containing methylmethac-monomers, such as Signum PEEK bond and Visio.link [ 67 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEEK frameworks have a grayish-brown or pearl-white opaque color and need to be veneered with a composite resin. Several studies on bond strength of PEEK with composite resins have proposed different pre-treatments such as airborne-particle abrasion, silica coating [ 63 ], piranha-etching [ 64 ], sulfuric acid [ 65 ], phosphoric acid or argon plasma [ 66 ] with conflicting results. However, most of the studies concluded that reliable bond strength to composite veneering resins and luting cements can be achieved when PEEK surfaces are pretreated and conditioned using adhesive systems containing methylmethac-monomers, such as Signum PEEK bond and Visio.link [ 67 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of CAD-CAM fabricated customized healing abutments and standard healing caps placed at the surgical stage for the creation of the desired emergence profile (n = 10/group) After a healing period of 1-3 months Patients with PEEK customized healing abutments showed higher functional implant prosthodontics score (FIPS) and lower numerical rating scale (NRS) values such as airborne-particle abrasion, silica coating [63], piranha-etching [64], sulfuric acid [65], phosphoric acid or argon plasma [66] with conflicting results. However, most of the studies concluded that reliable bond strength to composite veneering resins and luting cements can be achieved when PEEK surfaces are pretreated and conditioned using adhesive systems containing methylmethac-monomers, such as Signum PEEK bond and Visio.link [67][68][69][70][71].…”
Section: Randomized Clinical Trialmentioning
confidence: 99%
“…However, only histomorphometric data were reported, not focusing on the PEEK–soft tissue interface. PEEK has also been used to fabricate frameworks or abutments of fixed dental prosthesis with good chemical adhesion properties (Caglar, Ates, & Yesil Duymus, ; Stawarczyk et al, , ). Some properties using PEEK prosthetic abutments include high rigidity and low plaque affinity due to a high polishing capability and low porosity.…”
Section: Introductionmentioning
confidence: 99%
“…25 Caglar et al reported that using adhesive systems, including Visio.Link after sandblasting improved resin bonding to PEEK. 26 In the current study, the surface of indirect composites and PEEK were sandblasted with aluminum oxide particles according to the manufacturers' instructions to increase the bond strength. We also used Visio.Link bonding agent to achieve optimal bond strength between different veneering resins and PEEK.…”
Section: Discussionmentioning
confidence: 99%